Tobacco industry targeting Sri Lankan non-tobacco-growing farmers in corporate social investments - Buddhika, I.; Perera, K.M.N.; Lakmal, S.C.; Perera, C.S.; Wijesooriya, H.; Rajasuriya, M. (European Publishing, 2018)
Background: Sustainable Agriculture Development Project (SADP) is the main Corporate Social Investment (CSI) activity of the Ceylon Tobacco Company (CTC), the subsidiary of British American Tobacco holding cigarette manufacturing monopoly in Sri Lanka. In its initiation in 2006, its target group was tobacco farmers. By 2017, its beneficiaries included farmers other than tobacco growers. This study aimed to explore the process of tobacco industry increasing its coverage towards non-tobacco growers and its apparent benefits to the industry. Methods: A qualitative study design was used. Data were collected using document analysis (reports and presentations of CTC and CSI partners and media reports) and key informant (N=18) interviews (CTC CSI officers, field workers of government and non-government organisations, community leaders and beneficiaries of SADP programme). Documents from 2006 onwards were identified electronically and manually from databases, electronic archives and libraries. Search terms used were identified using an expert panel. Data were analysed using thematic analysis. Results: By 2017 four variations of SADP existed, all targeting non-tobacco growing farmers. Activities mainly included home gardening and infrastructure development in rural communities. A variation (SADP Lite) incorporated ex-libertarian combatants as part of their rehabilitation process by the government. Activities engaged ministers, government officials, field workers and community leaders. Key informants' perceptions included; CTC functions beyond the stigmatized image of a 'tobacco company' by expansion to different activities and themes; non-tobacco-growing farmers indirectly motivated to strengthen links with CTC by starting tobacco cultivation, activities are portrayed as government initiatives by incorporating government ministers, officials and field workers, and, most activities are portrayed as solutions for negative effects of tobacco cultivation (home-gardening, alternative crops and agro wells) and tobacco use (nutrition and rural economy). Conclusions: CTC uses SADP to promote their image, improve their stake in the economy and motivate farmers to grow tobacco
Keywords: Tobacco industry; Sri Lanka; farmers